Experiencing virtual reality for perspective-taking of blind and visually impaired learners - Heap, Tania; Kaplan-Rakowski, Regina; Archibald, Audon (Educational Technology ＆ Society, 2024)
Understanding blindness or imagining being blind can be challenging for individuals without visual impairments. One of the affordances of high-immersion virtual reality (VR) is its ability to build empathy and facilitate perspective-taking. VR can be potent when providing narrative, experience-laden education that exposes users to ideas and settings that may be beyond their immediate reach. This paper reports on a pilot study based on a series of workshops conducted at a university intended to give participants the opportunity to experience a VR non-fiction story, documenting the experience of a man who became blind after years of deteriorating vision. The workshops intended to trigger participants' interest in VR technology and brainstorm ways that VR can address equity and inclusion of individuals with visual disabilities in education and the workforce. Findings from survey responses and group discussions of 34 workshop attendees revealed that participants' general empathy levels slightly increased after the VR experience. Participants' perceptions of blind people's productivity significantly increased following the VR experience, suggesting that immersive technology can be integrated in various educational and training settings to enhance empathy and understanding of the experiences of diverse populations, including populations that are underrepresented in higher education and the workforce. This pilot study is a stepping stone for a larger project aiming to confirm the preliminary findings and to derive more exhaustive recommendations for educators and educational policy makers to address inclusion of people with visual disabilities in education and the workforce.